DELETIONAL POLYMORPHISM OF GLUTATHIONE TRANSFERASE T1 AND M1 GENES IN PATIENTS WITH MYOCARDIAL INFARCTION AND METABOLIC SYNDROME - V. A. Nevzorova; E. A. Panchenko; M. P. Isaeva (Кардиоваскулярная терапия и профилактика)
Aim. To study associations of deletional polymorphism of genes GSTM1 and GSTT1 with myocardial infarction (MI) development on the background of metabolic syndrome (MS).Material and methods. Totally 86 patients with STEMI were included (from those 45 had signs of MS) and 30 healthy persons as control. By polymerase chain reaction the data on deletional polymorphism was obtained on the genes coding glutathiontransferase GSTM1 and GSTT1 in both groups.Results. The significant increase of prevalence of genotype GSTT10/0 is ascertained in patients with MI and without MS; presence of the “null” genotype increases relative risk of infarction in both patients with and without MS. In the first group (without MS) presence of genotype GSTT10/0 leads to increase of MI risk irrespective of smoking status, though in MS patients — only in those who smokes.Conclusion. Diagnostic of homozygous deletional mutation GSTT1 can be used for individual prognosis of MI risk in patients with MI risk factors — smoking and MS.